The Quality of Lokan (Geloina erosa ) Rendang Oil Substituted with Red Palm Oil Olein - Budiyanto, Budiyanto; Anis, Ulfah; Jayadi, Iqbal; Syafnil, Syafnil (Department of Technology of Agricultural product (THP) Jambi University, 2023)
Rendang is a typical Minangkabau cuisine in West Sumatra, which is usually made with beef and other protein resources such as Lokan, which contains amino acids L-leucine and L-isoleucine. It is made with coconut milk that produces oil during cooking. The oil can be substituted with Red Palm Oil Olein (RPOO), which contains nutrients essential for the body as antioxidants. This study aims to determine the effect of RPOO substitution in Lokan rendang on color properties, vitamin A content, antioxidant activity, and organoleptic properties. A Completely Randomized Experimental Design (CRD) with one factor and five treatment levels was used in this study. Â The treatment factor was RPOO substitution with 0, 25, 50, 75, and 100% Lokan rendang oil. Each treatment was repeated three times resulting in 15 experimental runs. The data of vitamin A and antioxidant activity were analyzed using ANOVA followed by LSD, whereas sensory data were analyzed using the Friedman Ranking Test. The result showed that RPOO substitution significantly affected the antioxidant activity and organoleptic properties (taste, aroma, and overall) of rendang Lokan. The greater the substituted RPOO, the greater the vitamin A content in Lokan rendang. The substitution of 50% oil in rendang lokan with RPOO Â Â improved provitamin A and antioxidant activity significantly without disrupting the acceptability its sensory values. Therefore, the 50% substitution of rendang lokan oil can be utilized to fortify vitamin A.